Molecular relationships of the Australian Ennominae (Lepidoptera: Geometridae) and implications for the phylogeny of the Geometridae from molecular and morphological data - Young, Catherine J. (Zootaxa, 2006)
Molecular data from the 28S D2 ribosomal nuclear gene fragment were utilised to construct a phylogeny for the Australian Ennominae. Sequences were obtained from 68 geometrid and 5 outgroup species. Sequences from a smaller subset of 17 species also were analysed using the nuclear protein-coding gene EF-1a. Species were sampled from all major subfamilies of the Geometridae as no a priori assumptions could be made confidently about possible sister groups to the Australian Ennominae.The major findings from these analyses were as follows:(a) Drepanidae are a sister group to Geometridae;(b) Larentiinae are derived basally within the Geometridae; the Sterrhinae are the penultimate basally derived group;(c) Oenochrominae s. str. are closely related to the Geometrinae.(d) Ennominae are not monophyletic;(e) Tasmanian Archiearinae are misplaced in the Archiearinae and have close affinities to Australian Nacophorini (Ennominae);(f) Australian Nacophorini are not monophyletic.These results are at odds with traditionally held beliefs on the origins of Geometridae but are in broad agreement with and elaborate on the findings of Abraham et al. (2001). The implications of these findings in relation to key morphological characters are discussed using the proposed phylogenetic framework.